Análise ergonômica da atividade na execução do serviço de contrapiso - Gregolis, Caio Dantas (2021)
In Brazil, in particular, civil construction is a traditional industry that, despite the increasingly frequent technological and managerial innovations, the vast majority of work is still carried out manually. The association of functions that require the use of intense, repetitive physical efforts, improvised postures and body movements with inadequate conditions and low qualification can be harmful and cause damage to the health of workers. That said, the main objective of this work, which consists of evaluating the ergonomic conditions associated with the execution of the screed service, was built within this context from the identification of a knowledge gap and the need to disseminate the importance and impact of carrying out ergonomic analysis that can positively reflect on the worker's life. Three ergonomics assessment tools were used to carry out the analysis and obtain a diagnosis, which pointed out the ergonomic risks that the worker responsible for carrying out the screed was exposed, identifying the most critical steps and activities of this service. Such tools were: MET (The Standard Metabolic Equivalent), in which the energy expenditure was evaluated, REBA (Rapid Entire Body Assessment), in which the postures of the whole body in the use of activities were evaluated, and EWA (Ergonomic Workplace Analysis), in which the “Lifting of Loads” (physical factor), “Accident Risk” (organizational factor) and “Communication between Workers and Personal Contacts” (cognitive factor) were evaluated. In order to obtain this diagnosis, direct observations, interviews and photographic records, including filming, of workers and workstations for data collection were carried out, which were subsequently processed based on the listed ergonomic assessment tools. Among the results obtained with the realization of the case studies, the following stand out: "Materials Supply" and "Waste Removal" tasks predominating as heavy work (MET), a higher percentage of very high risk postures in the "Screed Layer Production” task, mainly during the activities of “smooth” and “rub” (REBA), and the “Mortar Production” task and “Load Lifting” factor presenting the biggest numbers of negative classifications (EWA). It is safe to affirm that the performance of the screed service presents evident ergonomic risks, especially those related to the postures required. This research proved to be contributory for notifying such risks, proposing improvements and highlighting the ergonomics associated with civil construction.